2024
DOI: 10.1097/gox.0000000000005565
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in Research Participation: Bias in Plastic Surgery Residency Match

Lawrence O. Lin,
Allyson L. Huttinger,
Paris Butler
et al.

Abstract: Background: Integrated plastic surgery residency applicants have increased at a rate disproportionate to available positions. Research productivity has become a surrogate marker for competitiveness, and many applicants pursue it to distinguish themselves. To date, no study has investigated socioeconomic disparities in extended research experience (ERE) participation. Methods: A 35-question cross-sectional survey was distributed to applicants to United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A recent survey examined trainees who engaged in extended research experiences before medical school, between the third and fourth years of medical school, or after medical school. 5 Trainees who pursue extended research experiences are more likely to be from Northeastern medical schools and have parents with more advanced degrees. 5 As programs continue to evaluate applicants, we encourage them to consider the potential bias for trainees of higher socioeconomic status to participate in extended research experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent survey examined trainees who engaged in extended research experiences before medical school, between the third and fourth years of medical school, or after medical school. 5 Trainees who pursue extended research experiences are more likely to be from Northeastern medical schools and have parents with more advanced degrees. 5 As programs continue to evaluate applicants, we encourage them to consider the potential bias for trainees of higher socioeconomic status to participate in extended research experiences.…”
Section: Discussionmentioning
confidence: 99%
“…5 Trainees who pursue extended research experiences are more likely to be from Northeastern medical schools and have parents with more advanced degrees. 5 As programs continue to evaluate applicants, we encourage them to consider the potential bias for trainees of higher socioeconomic status to participate in extended research experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This drastically increases their match probabilities, and studies have also found that IMGs that have matched into the integrated plastic surgery program have done at least 2 years of research fellowship. 38,39 It is noteworthy that for all applicant types, it has been found that letters of recommendation are the most important factor in the residency application. [40][41][42][43] The dedicated years of research fellowship enable them to gain reasonable mentorship and form meaningful relationships with their potential letters of recommendation writers.…”
Section: Discussionmentioning
confidence: 99%
“…A 2023 study reported socioeconomic biases present in accessing research fellowships, and that lack of monetary support was a main reason for not applying. 5 Further work is needed to address funding availability for fellowships, whether it be through industry sponsors, NIH grants, or partnerships with national plastic surgery organizations. Ultimately, when fellowships function as a pipeline for mentorship, clinical experiences, and a better chance of matching, it is critical to examine who has access.…”
mentioning
confidence: 99%